2020
DOI: 10.2174/1871520619666191024122117
|View full text |Cite
|
Sign up to set email alerts
|

Possible Selective Cytotoxicity of Vanadium Complex on Breast Cancer Cells Involving Pathophysiological Pathways

Abstract: Background: Triple-Negative Breast Cancers (TNBC) are among the most aggressive and therapyresistant breast tumors. Development of new treatment strategies that target pathways involved in cancer cells resistance is an attractive candidate to overcome therapeutic resistance. Objective: To clarify the antitumor activity of [VO (bpy)2 Cl] Cl complex as a new therapeutic agent through studying the interplay between apoptosis, autophagy and notch signaling pathways. Methods: Proliferation of MDA-MB-231 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In another study, we have found that an oxidovanadium complex with quinolinium cation (66) induced autophagic process in pancreatic cancer cells with simultaneous increase in the RAGE protein level [79]. Autophagy was also detected in vanadium-treated (90) breast cancer cells [101]. An interesting study has been performed in hypoxic conditions.…”
Section: Programed Cell Deathmentioning
confidence: 97%
See 1 more Smart Citation
“…In another study, we have found that an oxidovanadium complex with quinolinium cation (66) induced autophagic process in pancreatic cancer cells with simultaneous increase in the RAGE protein level [79]. Autophagy was also detected in vanadium-treated (90) breast cancer cells [101]. An interesting study has been performed in hypoxic conditions.…”
Section: Programed Cell Deathmentioning
confidence: 97%
“…Oral squamous cell carcinoma Cal27 Induction of apoptosis: poly(ADPribose)polymerase cleavage Autophagy was also detected in vanadium-treated (90) breast cancer cells [101]. An interesting study has been performed in hypoxic conditions.…”
Section: Structure Mechanism Referencesmentioning
confidence: 99%
“…Nevertheless, cytokines could conversely promote or inhibit the progression of autophagy (Jiang et al., 2019). Moreover, TGF‐β is a common regulator that mediates the cross talk between autophagic and apoptotic cell death (El‐Shafey & Elsherbiny, 2019a, El‐Shafey and Elsherbiny, 2019b; Wu et al., 2016). Thus, reduction of its level can suppress CsA‐induced renal apoptosis and promote renal‐protective activities of sidr and flaxseeds.…”
Section: Discussionmentioning
confidence: 99%
“…Cell suspension (100 µl) was taken in another 5 ml test tube, then, 5 µl of annexin V (FITC label) and 5 µl PI (PE label) were added directly. The mixture was incubated for at least 15 min in the dark at 37°C then cells were re‐dissolved in 200 µl 1× binding buffer and analyzed (El‐Shafey & Elsherbiny, 2019a).…”
Section: Methodsmentioning
confidence: 99%
“…Compounds containing the transition metal vanadium enhance redox reactions and interactions with nucleic acids, which promote mechanisms of cell death such as cell cycle arrest and DNA damage in various cancer types. [172,173] Recent studies in MDA-MB-231 cells have shown apoptotic and autophagic cell death with notch pathway inhibition of a vanadium-based complex, compound 58, a oxidovanadium (IV) complex by Gonzalez-Baró and co-workers with a chelating ligand made from the condensation reaction of o-vanillin and 2thiophenemethylamine. [174] Cellular studies in MDA-MB-231 cells showed cytotoxicity (IC 50 = 29 � 1.7 μM, 48 h), an apoptotic cell death, antimigratory activity, and increased ROS production.…”
Section: Vanadium Compoundsmentioning
confidence: 99%